Can central and local forces promote green innovation of heavily polluting enterprises? evidence from China - Yang, Guang; Zhang, Jijian; Zhang, Jize (Frontiers in Energy Research, 2023)
Adequate government environmental supervision is the key to promoting green innovation which is an essential driver of green development. In environmental decentralization, an analysis of the mechanism of the inherent influence of central and local supervision on green innovation may prove to be of practical importance. The paper selects data from heavily polluting enterprises in A-shares in China from 2013 to 2019 for analysis. These conclusions are: 1. Both central and local supervision can significantly facilitate green innovation in heavily polluting enterprises. Local supervision has a weaker promotion effect than central supervision. 2. The two environmental supervision approaches can work synergistically. Central supervision can enhance the effect of local supervision on enterprises' green innovation. 3. An analysis of heterogeneity indicates that the two environmental supervision approaches significantly promote eastern heavy polluters engage into green innovation. However, they do not promote it significantly for non-eastern enterprises. In addition, the same regional heterogeneity exists in the positive moderating effect of central supervision. 4. Further research finds that both types of supervision induce high-quality substantive green innovation.Central supervision can further enhance the impact of local supervision on enterprises' substantive green innovation. The paper provides empirical data references for establishing an environmental supervision path under collaboration by governments at different levels, and offers implications for advancing high-quality green innovation in heavy polluters.